2005
DOI: 10.2337/diacare.28.6.1383
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy Is Associated With Mortality and Cardiovascular Disease Incidence

Abstract: OBJECTIVE -To study the relationship of nonproliferative and proliferative retinopathy with all-cause mortality and cardiovascular disease (CVD) incidence in type 1 diabetic patients and, additionally, the role of cardiovascular risk factors in these associations. RESEARCH DESIGN AND METHODS-This prospective study included 2,237 type 1 diabetic patients from 31 centers in 16 European countries at baseline, aged 15-60 years, who were examined for retinopathy by taking two-field 45°fundus photographs, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
5
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 38 publications
12
93
5
2
Order By: Relevance
“…Studies in Finland (10,16) and Milan (11) have reported an increased CHD risk among diabetic individuals with retinopathy, while controlling for cardiovascular risk factors. Other studies, however, suggest that the association of diabetic retinopathy with CHD is largely due to shared risk factors (12,13,15). A recent study of 824 type 2 diabetic patients, using fundoscopic examinations to evaluate retinopathy, showed a sex difference in the association of background diabetic retinopathy with CHD death, raising the possibility that microvascular disease might be more important in the development of CHD in women than in men (16).…”
Section: Discussionmentioning
confidence: 91%
“…Studies in Finland (10,16) and Milan (11) have reported an increased CHD risk among diabetic individuals with retinopathy, while controlling for cardiovascular risk factors. Other studies, however, suggest that the association of diabetic retinopathy with CHD is largely due to shared risk factors (12,13,15). A recent study of 824 type 2 diabetic patients, using fundoscopic examinations to evaluate retinopathy, showed a sex difference in the association of background diabetic retinopathy with CHD death, raising the possibility that microvascular disease might be more important in the development of CHD in women than in men (16).…”
Section: Discussionmentioning
confidence: 91%
“…In fact, substantial evidence now exists that both microalbuminuria and retinopathy are independent risk factors for CVD events and mortality (2)(3)(4)(5)(7)(8)(9)(10)(11)30). Although the studies in type 1 diabetes are limited in number (9,31), this relationship between retinopathy and CVD is present in both type 1 and type 2 diabetic populations and appears strongest for proliferative retinopathy (4,5,7-11).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This relationship appears to be present in both type 1 and type 2 diabetes (4 -11). Importantly, most (4,5,(7)(8)(9)(10)(11), but not all (9), of these studies have indicated that retinopathy may be independently associated with CVD events or mortality even after taking into account standard cardiovascular risk factors, diabetes duration, and/or glycemic control. Results from these studies suggest that there may be shared risk factors or mechanisms underlying both retinopathy and clinical CVD and that the relationship does not appear to be explained by standard cardiovascular risk factors or glycemic control.…”
mentioning
confidence: 99%
“…Diabetic retinopathy is also associated with mortality and cardiovascular disease incidence in diabetes [2]. Prospective studies identified poor glycemic control, duration of diabetes and blood pressure as most important risk factors for development of retinopathy [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%